Therapeutic effect and risk factors for postoperative complications of endoscopic negative pressure ligation combined with sclerotherapy injection for internal hemorrhoid bleeding - SHEN Baolong*, LUAN Xiaolin, LI Longbin, REN Bin (Zhongguo linchuang yanjiu)
Objective To investigate the clinical efficacy of endoscopic negative pressure ligation combined with sclerotherapy in the treatment of internal hemorrhoidal hemorrhage, and to analyze the risk factors of postoperative complications. Methods A total of 210 patients with grade Ⅱ to Ⅲ internal hemorrhoids admitted to the Department of Colorectal Surgery of our hospital from March 2021 to March 2023 were randomly divided into a control group (105 cases) and a combination group (105 cases) using a digital table method. The control group received endoscopic negative pressure ligation treatment, while the combination group received endoscopic negative pressure ligation combined with sclerotherapy injection treatment. The surgical treatment efficacy and postoperative complications of the two groups of patients were compared. According to the incidence of postoperative complications, patients were divided into complication group and non complication group, and logistic multiple regression analysis was used to identify the risk factors for postoperative complications in patients. Results The total effective rate of the combined group was higher than that of the control group, the difference was statistically significant (97.14% vs 86.67%, P＜0.05). The operative time of the combined group was longer than that of the control group, the intraoperative blood loss was lower than that of the control group, the internal hemorrhoidal shedding time and hospital stay were shorter than that of the control group, and the total incidence of complications was lower than that of the control group, the difference was statistically significant (P＜0.05). Multivariate logistic regression analysis showed that age ≥50 years old, duration ≥1 year, degree Ⅲ of internal hemorrhoids, spicy diet, shedding time ≥7 d and first defecation time＜24 h were all independent risk factors for postoperative complications of internal hemorrhoids (P＜0.05). Conclusion Endoscopic negative pressure ligation combined with sclerosing agent injection has good clinical effect and low complication rate. Advanced age, long course of disease, severe prolapse degree of internal hemorrhoids, spicy diet, long time of internal hemorrhoids loss, and premature first defecation are all risk factors for postoperative complications of internal hemorrhoids. Effective intervention measures should be developed by acupuncture above risk factors to improve the therapeutic effect of surgery.